Pengaruh Lama Pengeringan Daun Cemcem (Spodiaz pinnata LF Kurz) Terhadap Aktivitas Antioksidan Dan Sifat Sensoris Teh Celup Herbal - Yunia Angelia Putri, Putu; Kartika Pratiwi, I Desak Putu; Kadek Diah Puspawati, I Gusti Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2023)
This research aimed was to determine the effect of drying time on the antioxidant and sensory activity of Cemcem leaf tea bags (Spodiaz pinnata LF Kurz) and to determine the appropriate drying time to produce the best antioxidant activity and sensory properties. This study used a randomized block design with drying time treatment consisting of 5 levels: 180 minutes, 210 minutes, 240 minutes 270 minutes and 300 minutes. Each treatment was repeated 3 times in order to obtain 15 experimental units. The data obtained were analyzed using variance and if there was an effect, it was continued with the Duncan Multiple Range Test. The results showed that the drying time had a significant effect (P<0.01) on water content, ash content, water solubility, antioxidant activity, total phenol and sensory (color, flavor, taste) of cemcem leaf teabags. The drying time of 180 minutes resulted in the best cemcem leaf teabags with characteristics: water content of 11.2%, ash content of 8.85%, extract content in water 7.18%, antioxidant activity of 81.06%, IC50 of 78.7 ppm, total phenol 44 mgQE / g with the with the sensory characteristic of tea brewing, the color is a greenish yellow and liked, the aroma is typical of cemcem leaves and slightly liked, the taste is sour and slightly liked, and the overall acceptance liked.